The effects of chemogenetic targeting of serotonin-projecting pathways on L-DOPA-induced dyskinesia and psychosis in a bilateral rat model of Parkinson’s disease - Lipari, Natalie; Galfano, Ashley; Venkatesh, Shruti; Grezenko, Han; Sandoval, Ivette M.; Manfredsson, Fredric P.; Bishop, Christopher (Frontiers in Neural Circuits, 2024)
Parkinson's Disease (PD) is commonly characterized by severe dopamine (DA) depletion within the substantia nigra (SN) leading to a myriad of motor and non-motor symptoms. One underappreciated and prevalent non-motor symptom, Parkinson's disease-associated psychosis (PDAP), significantly erodes patient and caregiver quality of life yet remains vastly understudied. While the gold standard pharmacotherapy for motor symptoms Levodopa (LD) is initially highly effective, it can lead to motor fluctuations like LDinduced dyskinesia (LID) and non-motor fluctuations such as intermittent PDAP. One source of these fluctuations could be the serotonergic raphe nuclei and their projections. Serotonin (5-HT) neurons possess the machinery necessary to convert and release DA from exogenous LD. In DA-depleted brain regions these 5-HT projections can act as surrogates to the DA system initially compensating but chronically leading to aberrant neuroplasticity which has been linked to LID and may also contribute to non-motor fluctuations. In support, recent work from our lab established a positive relationship between LID and PDAP in parkinsonian rats. Therefore, it was hypothesized that normalizing 5-HT forebrain input would reduce the co-expression of LID and PDAP. To do so, we expressed 5-HT projection specific inhibitory designer receptor exclusively activated by designer drugs (DREADDs) using Cre-dependent AAV9-hM4di in tryptophan hydroxylase 2 (TPH2)-Cre bilaterally 6-OHDA-lesioned rats. Thereafter we used the designer drug Compound 21 to selectively inhibit 5-HT raphe projections during LD treatment to modulate the expression of PDAP, assayed by prepulse inhibition (PPI) and LID, quantified by the abnormal involuntary movements (AIMs) test. Our results suggest that chemogenetic inhibition of 5-HT raphe-projecting cells significantly reduces LID without affecting stepping ability or established sensorimotor gating deficits. Overall, this study provides further evidence for the complex influence of 5-HT rapheprojecting neurons on LD's neurobehavioral effects.